PENGOLAHAN AIR PAYAU MENGGUNAKAN TEKNOLOGI OSMOSA BALIK - widayat, wahyu; yudho, satmoko (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2002)
Tanjung Aru is a village located in cape of Tanjung Aru, East Kalimantan. The community living in Tanjung Aru use surface water from wells as the main clean water resource. The surface water is so influenced by the tide of sea water. The surface taste is very salty (DHL>1500 mMhos/cm). The water is not only salty but also the turbidity is much more than water quality standart. The use of rain water as the second alternative is very limited, it is only in rainy season.To deal with the chronic problem, such as the lack of clean water supply, it needs an appropriate water treatment technology. The suitable water treatment system is a combination of conventional and advanced technology. Desalination, such as Reverse Osmosis must be involved to reduce salinity of the raw water. A complete process includes the pretreatment and advance treatment. The pretreatment are oxidation and some common filtrations. The advance treatment is a molecular filtration using a membran which the principal is reverse osmosis pressure. If the pilot water treatment plant is avalaible in Tanjung Aru, the clean water supply will not be a serious problem. Generally, it can also play an important role to increase the social level of community in East Kalimantan.